SEHATI PROGRAM: A FLEXIBLE MODEL FOR EFFECTIVE HALAL CERTIFICATION - Nur Kasanah; Rosita Novi Andari (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2024)
Abstract This field research, employing a descriptive qualitative approach, explores the innovation in implementing the Sehati program by the Office of Religious Affairs (KUA) of Taman District, Madiun City. The program facilitates and accelerates the free halal certification process for Micro and Small Businesses (MSEs) in Taman District, Madiun City, during 2021-2023. Data was collected through document analysis, interviews, and observations with KUA officials, Halal Product Process Assistants (P3H), and MSE actors who participated in the Sehati acceleration program. The findings indicate that the KUA of Taman District innovated in the Sehati program by managing flexible service business processes, strengthening the role of Islamic religious instructors as P3H, collaborating with agencies related to MSEs, involving madrasahs within the KUAΓÇÖs jurisdiction, and promoting MSEs with issued halal certificates. As a result, eight P3H successfully assisted 773 MSE actors and issued 508 halal certificates. Halal labels on MSE products improved product packaging, increased consumer confidence, and expanded marketing areas, leading to higher business turnover. This innovation can serve as a reference for implementing the Sehati program in other regions in Indonesia, thereby accelerating the achievement of halal certification as a primary guarantee of MSE product quality in Indonesia. Abstrak Penelitian lapangan dengan pendekatan kualitatif deskripstif ini bertujuan untuk mengeksplorasi inovasi implementasi program Sehati yang dilakukan oleh Kantor Urusan Agama (KAU) Kecamatan Taman Kota Madiun dalam memfasilitasi dan mengakselerasi proses sertifikasi halal gratis bagi pelaku Usaha Mikro dan Kecil (UMK) di Kecamatan Taman Kota Madiun selama periode tahun 2021-2023. Pengumpulan data dilakukan melalui metode analisis dokumen, wawancara dan observasi dengan pejabat KUA, Pendamping Proses Produk Halal (P3H) dan pelaku UMK di wilayah Kecamatan Taman Kota Madiun yang telah mengikuti program akselerasi Sehati. Hasil penelitian menunjukkan bahwa KUA Kecamatan Taman Kota Madiun melakukan inovasi dalam implementasi program Sehati melalui manajamen proses bisnis layanan yang fleksibel yaitu dengan cara penguatan peran penyuluh agama Islam sebagai P3H, kerjasama dengan instansi yang berkaitan dengan UMK, pelibatan madrasah yang berada di wilayah kerja KUA Kecamatan Taman Kota Madiun, dan publikasi UMK yang sudah terbit sertifikat halalnya. Hasil inovasi implementasi tersebut yaitu terdapat delapan P3H yang telah berhasil mendampingi 773 pelaku UMK dan menerbitkan 508 sertifikat halal, dan adanya label halal pada produk UMK berdampak pada perbaikan kemasan produk, meningkatnya kepercayaan konsumen, dan perluasan wilayah pemasaran yang berdampak pada kenaikan omzet usaha. Inovasi ini dapat menjadi acuan bagi praktik implementasi program Sehati di daerah lainnya di Indonesia sehingga dapat mengakselerasi capaian sertifikasi halal sebagai jaminan utama kualitas produk UMK di Indonesia.